Increased physical activity, higher educational attainment, and the use of mobility aid are associated with self-esteem in people with physical disabilities - Alhumaid, Majed M.; Said, Mohamed Ahmed (Frontiers in Psychology, 2023)
Background: High self-esteem can help people with disabilities overcome barriers and improve their mental health and well-being. This study sought to examine self-esteem levels among Saudis with physical disabilities based on socio-economic factors. It also aimed to determine the minimum weekly duration of physical activity performed by participants and examine its effects, along with those of other socio-economic factors, on participants' self-esteem. Methods: A participant sample (N = 582) consisting of Saudi individuals aged 33.78 ± 9.81 years with physical disabilities (males, n = 289; females, n = 293) was recruited to participate in this study. Levels of self-esteem were measured using the Arabic version of the Rosenberg Self-Esteem Scale. Results: Compared to women, men demonstrated significantly higher levels of overall self-esteem, positive feelings, and negative feelings (p < 0.01). The respondents' average levels of overall self-esteem (p < 0.001), positive feelings (p < 0.01), and negative feelings (p < 0.001) also varied by type of physical disability. Wheelchair-using participants had the highest values for self-esteem and positive feelings; cane-using participants or those who did not use mobility aids had the lowest values. Weighted least squares regression showed that weekly physical activity was the factor that most affected self-esteem (β = 0.002), followed by education level (β = 0.115), then type of mobility device used (β = -0.07). Conclusions: Increased weekly physical activity, higher education levels, and the use of mobility aids were the factors likely to improve the self-esteem of Saudis with physical disabilities.